Reviving Moroccan Tourism Amid the COVID-19 Pandemic: Challenges for Tourism Institutions - Saber, Mohamed Reda (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
This thesis aims to identify the COVID-19's impact and challenges for tourism institutions in Morocco, the sudden interruption of national and international flights and the closure of the entire tourism sector due the pandemic COVID-19 crisis have resulted in a negative stoppage of activity. The COVID-19 crisis is a mix of a crisis. To prevent further spread of COVID-19, governments around the world have taken radical action such as closing entire countries, causing a massive shock to the global tourism industry. For hotels and airlines, the COVID-19 virus is forcing, times are very hard. The importance of jobs and contribution to the economy in general is critical, particularly for country like Morocco, where activity is important to the economy. The primary objective of this study is to propose a long-term reflection for a global revision of the Moroccan tourism model. In this revision, domestic demand should be placed at the center of the system, rather than always being seen as a simple palliative. The results of the analysis revealed that the major challenges confronting the tourism industry due to COVID-19 are; health and safety concerns, challenges in reopening doors of all tourism sectors, in face of national and international Customer, and travel restrictions. The “Welcome Safely” label, based on the health safety in the context of prevention related to COVID-19 for Moroccan tourist establishments, in collaboration with the authorities competent Moroccan sanitary facilities. Keywords: COVID-19 Pandemic, Post-COVID-19, Morocco, Hospitality Industry, Tourism Sector, Domestic Tourism, Risk Management.

ÖZ: Bu tez, COVID-19'un Fas'taki turizm kurumları üzerindeki etkisini ve zorluklarını, ulusal ve uluslararası uçuşların aniden kesilmesi ve pandemi COVID-19 krizi nedeniyle tüm turizm sektörünün kapatılmasının olumsuz bir faaliyet durmasına neden olduğunu belirlemeyi amaçlamaktadır. COVID-19 krizi, bir krizin karışımıdır. COVID-19'un daha fazla yayılmasını önlemek için dünyanın dört bir yanındaki hükümetler, tüm ülkeleri kapatmak gibi radikal önlemler alarak küresel turizm endüstrisinde büyük bir şoka neden oldu. Oteller ve havayolları için COVID-19 virüsü zorluyor, zamanlar çok zor. İstihdamın önemi ve genel olarak ekonomiye katkı, özellikle faaliyetin ekonomi için önemli olduğu Fas gibi ülkeler için çok önemlidir. Bu çalışmanın birincil amacı, Fas turizm modelinin küresel bir revizyonu için uzun vadeli bir yansıma önermektir. Bu revizyonda iç talep her zaman basit bir palyatif olarak görülmek yerine sistemin merkezine yerleştirilmelidir. Analiz sonuçları, COVID-19 nedeniyle turizm endüstrisinin karşılaştığı başlıca zorlukların; sağlık ve güvenlik endişeleri, ulusal ve uluslararası Müşteri karşısında tüm turizm sektörlerinin kapılarının yeniden açılmasındaki zorluklar ve seyahat kısıtlamaları. Yetkili Fas sıhhi tesisleri ile işbirliği içinde, Fas turizm işletmeleri için COVID-19 ile ilgili önleme bağlamında sağlık güvenliğine dayanan “Güvenle Hoş Geldiniz” etiketi. Anahtar Kelimeler: COVID-19 Pandemisi, COVID-19 Sonrası, Fas, Konaklama Endüstrisi, Turizm Sektörü, Iç Turizm, Risk Yönetimi.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2022. Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism Faculty; Tourism--COVID 19 Pandemic--Morocco; COVID-19--Economic aspects; COVID-19 Pandemic, 2020-; Tourists--Travel--Covid 19 Pandemic--Morocco; COVID-19 Pandemic; Post-COVID-19; Morocco; Hospitality Industry; Tourism Sector; Domestic Tourism; Risk Management